2007
DOI: 10.1212/01.wnl.0000260064.77700.fd
|View full text |Cite
|
Sign up to set email alerts
|

MRI outcomes in a placebo-controlled trial of natalizumab in relapsing MS

Abstract: Natalizumab has a sustained effect in preventing the formation of new lesions in patients with relapsing multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
205
2
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(235 citation statements)
references
References 23 publications
20
205
2
8
Order By: Relevance
“…In the patients receiving natalizumab, this finding might be caused by the well-known pseudoatrophy effect, in which the anti-inflammatory effect of natalizumab reduces the edema during the first 12 months of treatment. 9,29,30 Clinically, natalizumab appeared to stabilize EDSS scores and reduce symptoms of depression, as observed in our data. No effect on cognitive functioning was found in this study.…”
Section: Discussionsupporting
confidence: 86%
“…In the patients receiving natalizumab, this finding might be caused by the well-known pseudoatrophy effect, in which the anti-inflammatory effect of natalizumab reduces the edema during the first 12 months of treatment. 9,29,30 Clinically, natalizumab appeared to stabilize EDSS scores and reduce symptoms of depression, as observed in our data. No effect on cognitive functioning was found in this study.…”
Section: Discussionsupporting
confidence: 86%
“…149 In the phase III placebo-controlled natalizumab trial in patients with RRMS, the patients receiving active therapy had a higher rate of brain volume loss in the first year than patients receiving a placebo, whereas the opposite was seen in the second year. 146 Similarly, in patients receiving autologous hematopoietic stem cell transplantation, a faster rate of brain volume loss was observed in the first few months than in the pre-treatment period. 147 However, subsequently, the treatment appears to slow the rate of atrophy.…”
Section: Brain Atrophymentioning
confidence: 96%
“…145 Atrophy measures are being incorporated into studies that explore the efficacy and safety of novel MS therapies. New data have emerged from natalizumab, 146 autologous hematopoietic stem cell transplantation, 147,148 and testosterone. 149 In the phase III placebo-controlled natalizumab trial in patients with RRMS, the patients receiving active therapy had a higher rate of brain volume loss in the first year than patients receiving a placebo, whereas the opposite was seen in the second year.…”
Section: Brain Atrophymentioning
confidence: 99%
“…Some studies have reported no significant, or conflicting, effects of DMTs on brain atrophy (Bermel & Bakshi, 2006; Calabrese et al., 2012; Lublin et al., 2016; Tiberio et al., 2005). Others have reported statistically significant slowing of brain atrophy, but only after 24 months or more (Cohen et al., 2012; Coles et al., 2012; Kappos et al., 2010; Mattioli, Stampatori, Bellomi, Scarpazza, & Capra, 2015; Miller et al., 2007; Rinaldi et al., 2012). Brain atrophy is considered predictive of progression in cognitive and/or motor disability (Bermel & Bakshi, 2006; Deloire et al., 2011; Morgen et al., 2006), emphasizing a need for early intervention to prevent brain atrophy and forestall the advance of disability.…”
Section: Introductionmentioning
confidence: 99%